Thinking ecologically : the next generation of environmental policy - Chertow, Marian R.; Esty, Daniel C. (Yale fastback., 1997)
"Twenty-five years ago, the Cuyahoga River in Ohio was so contaminated that it caught fire, air pollution in some cities was thick enough to taste, and environmental laws focused on the obvious enemy: large American factories with belching smokestacks and pipes gushing wastes. Federal legislation has succeeded in providing cleaner air and water, but we now confront a different set of environmental problems--less visible and more subtle. This important book offers thought-provoking ideas on how America can respond to changing public health and ecological risks and create sound environmental policy for the future. The innovative thinkers of the Next Generation Project of the Yale Center for Environmental Law and Policy--experts from business, government, nongovernmental organizations, and academia--propose reforms that balance environmental efforts with other public needs and issues. They call for new foundations for environmental law and policy, adoption of a more diverse set of policy tools and strategies (economic incentives, ecolabels), and new connections between critical sectors (agriculture, energy, transportation, service providers) and environmental policy. Future progress must involve not only officials from the U.S. Environmental Protection Agency and state environmental protection departments, say the authors, but also decision-makers as diverse as mayors, farmers, energy company executives, and delivery route planners. To be effective, next-generation policy-making will view environmental challenges comprehensively, connect academic theory with practical policy, and bridge the gaps that have caused recent policy debates to break down in rancor. This book begins the process of accomplishing these challenging goals"--